PENGARUH PERMAINAN SNOWBALL TERHADAP PENGETAHUAN TENTANG MENARCHE PADA SISWI KELAS 4 DAN 5 - Dwi Helynarti Syurandhari; Eka Diah Kartiningrum; Asih Media Yuniarti; Bella Febriyanti Fitriana (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Early menarche is a reproductive health problem in Asian countries, including Indonesia. The age of menarche should be 13-14 years old but the age of menarche in Indonesia is 9 years old, increasing every year 0.145. Unreadiness age will affect mental readiness in facing menarche. The study aimed to determine the effect of educational media on the knowledge and attitudes of female students about menarche at SDN Kedungmaling Sooko Mojokerto Regency. This study used quantitative type with quasi experimental method in pretest-posttest design. The sample size was 43 with a total population of 60. The data collected by used questionnaire and then analyzed by using the Wilcoxon test. The results of the Wilcoxon test stated that there were changes in knowledge (p value = 0.000 <0.005) and attitudes (p value = 0.000 <0.005) before and after the snowball game intervention. Snowball game educational media is effective for school-age children, based on the results of the crosstab there was a change in knowledge from poor to good (70%) Children learning style has a character that involves the senses of hearing, vision, good concentration and collaboration of locomotif so that snowball games are appropriate for children. Students are expected to more to seek information about menarche, so that it could be have a good impact on readiness to face menarche.